2007
DOI: 10.1111/j.1523-536x.2007.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing and Predictors of Postpartum Return to Smoking in a Group of Inner‐City Women: An Exploratory Pilot Study

Abstract: Almost one-half of the women in this pilot study who stopped smoking cigarettes during pregnancy resumed in the days immediately after delivery. These data suggest that future studies should explore the initiation of postpartum relapse prevention during the prenatal and perinatal period. Interventions may be more effective if they include strategies aimed increasing breastfeeding rates and assisting household members to stop smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Women's qualitative descriptions of their relapse experiences highlighted the infl uence of stress and a dearth of skills needed to manage stress. Our fi ndings are similar to a qualitative study ( Letourneau et al, 2007 ) conducted with inner-city women, in which stress was the most commonly cited reason for postpartum return to smoking. Clinicians might consider helping women to monitor their stress levels postpartum; women could benefi t from being taught strategies to cope with elevated stress.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Women's qualitative descriptions of their relapse experiences highlighted the infl uence of stress and a dearth of skills needed to manage stress. Our fi ndings are similar to a qualitative study ( Letourneau et al, 2007 ) conducted with inner-city women, in which stress was the most commonly cited reason for postpartum return to smoking. Clinicians might consider helping women to monitor their stress levels postpartum; women could benefi t from being taught strategies to cope with elevated stress.…”
Section: Discussionsupporting
confidence: 75%
“…A longitudinal study of 87 women who quit smoking during pregnancy found that elevated Beck Depression Inventory (BDI) scores at the end of pregnancy were associated with an increased risk of relapse by 6 months ( Solomon et al, 2007 ); the BDI was not administered after delivery. A qualitative study of 49 inner-city women who stopped smoking before or during pregnancy found that those who relapsed postpartum reported that stress was the primary reason for their return to smoking ( Letourneau et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of several studies suggest that breast feeding may protect against postpartum smoking relapse (Kaneko et al, 2008;Letourneau et al, 2007;Martin et al, 2008;O'Campo, Faden, Brown, & Gielen, 1992;Ratner, Johnson, & Bottorff, 1999;Ratner, Johnson, Bottorff, Dahinten, & Hall, 2000). However, the methodologies predominant in this literature often do not permit a clear inference because smoking and breast feeding are measured during either the same or the overlapping periods of time without identifying the timing of the status change (Kaneko et al;Martin et al;O'Campo et al;Ratner et al, 1999Ratner et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…22,27 Social disadvantage also increases the chances of living with a partner who smokes, 27,28 and the smoking status of partners and other household members is a predictor of maternal smoking habits before and during pregnancy, 29,30 and of returning to smoking after birth. 27,31,32 Findings from the Millennium Cohort Study 33 indicate that 70% of partners of women who smoked in pregnancy also smoked and that > 70% of these partners neither cut down nor quit. Underscoring the role of partners, maternal smoking in pregnancy is associated with difficulties in the relationship with the partner.…”
Section: Epidemiology Of Smoking In Pregnancymentioning
confidence: 99%
“…partners, family and friends) are recognised as important barriers to sustained quitting, 27,31,50 but these remain relatively under-researched in relation to smoking in pregnancy. Partners' smoking status and attitudes to smoking cessation are identified as…”
Section: Significant Others' Perspectivesmentioning
confidence: 99%